Intrauterine Fetal Death and the COVID-19 Pandemic: Looking beyond SARS- CoV-2 Infection (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: COVID-19 pandemic has caused high numbers of deaths and complications since 2020. Though the risk is the same as in the general population, pregnant women with COVID-19 are especially susceptible to developing complications because of their altered physiology. The objective of this retrospective study is to investigate the relationship betweenthe COVID-19 pandemic period and intrauterine fetal death, which can help to take steps to reduce intrauterine fetal death during the pandemic. Materials and methods: This retrospective study compared the intrauterine fetal death rate during the pre-pandemic (March 01, 2019 to February 29, 2020) and the pandemic period (March 01, 2020, to February 28, 2021) in a tertiary referral hospital in Bangladesh. Patient data were collected from the record-keeping register of the Department of Obstetrics and Gynecology and analyzed by computer-based software presented in graph, chart and table. Results: Out of 21717 obstetric patients admitted patients,821 (3.78%) were documented as cases of intrauterine fetal death in the pre-pandemic period, whereas in the pandemic period, the number was 895 (4.86%) out of 18424. Due to inadequate data records and considering the exclusion criteria, a total of 790 IUFD patients of the pre-pandemic period and 860 IUFD patients of the pandemic period were included in this study. Conclusion: The percentage of IUFD on obstetric admission showed significantly (p